MMP inhibitors attenuate doxorubicin cardiotoxicity by preventing intracellular and extracellular matrix remodelling - Chan, Brandon Y H (Cardiovasc Res, 2020)
AIMS: Heart failure is a major complication in cancer treatment due to the cardiotoxic effects of anticancer drugs, especially from the anthracyclines such as doxorubicin (DXR). DXR enhances oxidative stress and stimulates matrix metalloproteinase-2 (MMP-2) in cardiomyocytes. We investigated whether MMP inhibitors protect against DXR cardiotoxicity given the role of MMP-2 in proteolyzing sarcomeric proteins in the heart and remodelling the extracellular matrix. METHODS AND RESULTS: Eight-week-old male C57BL/6J mice were treated with DXR weekly with or without MMP inhibitors doxycycline or ONO-4817 by daily oral gavage for 4 weeks. Echocardiography was used to determine cardiac function and left ventricular remodelling before and after treatment. MMP inhibitors ameliorated DXR-induced systolic and diastolic dysfunction by reducing the loss in left ventricular ejection fraction, fractional shortening, and E′/A′. MMP inhibitors attenuated adverse left ventricular remodelling, reduced cardiomyocyte dropout, and prevented myocardial fibrosis. DXR increased myocardial MMP-2 activity in part also by upregulating N-terminal truncated MMP-2. Immunogold transmission electron microscopy showed that DXR elevated MMP-2 levels within the sarcomere and mitochondria which were associated with myofilament lysis, mitochondrial degeneration, and T-tubule distention. DXR-induced myofilament lysis was associated with increased titin proteolysis in the heart which was prevented by ONO-4817. DXR also increased the level and activity of MMP-2 in human embryonic stem cell-derived cardiomyocytes, which was reduced by ONO-4817. CONCLUSIONS: MMP-2 activation is an early event in DXR cardiotoxicity and contributes to myofilament lysis by proteolyzing cardiac titin. Two orally available MMP inhibitors ameliorated DXR cardiotoxicity by attenuating intracellular and extracellular matrix remodelling, suggesting their use may be a potential prophylactic strategy to prevent heart injury during chemotherapy.